(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Effective communication and collaboration between nurses and paramedics are essential for delivering high-quality care in emergency and critical care settings. This case study examines the impact of nurse-paramedic collaboration on patient outcomes through a real-life scenario involving the management of acute myocardial infarction. The study highlights the importance of clear and concise handovers, standardized communication tools, real-time collaboration platforms, and interprofessional training in facilitating seamless transitions of care. By leveraging these strategies, nurses and paramedics can optimize treatment outcomes, minimize delays, and improve patient survival and quality of life. This case study underscores the critical role of interdisciplinary teamwork in enhancing the delivery of emergency medical services and emphasizes the need for continued investment in communication skills and interprofessional education.